Scenarios in fashion collection development: from the tradition of industrial design to imagination (ModaPalavra e-periódico, 2023)
The essay discusses the process of scenario building in fashion design. It criticizes the methodologies used in this disciplinary field, whose foundations, at least in part, are situated in the tradition of industrial design. To do so, it compares Löbach’s (2001) proposal for industrial product configuration with Treptow’s (2013) proposal for collection development, highlighting structural similarities. Therefore, the essay demonstrates the possibility for fashion design to seek alternative paths to the tradition of industrial design, by valuing the potential for imagination that is inherent in scenarios. This possibility is illustrated through the case of Melissa, interpreted as an emblematic example of an organization that operates through scenarios in the development of a collection, and collection after collection, in the construction of its brand identity. The essay proposes opening a dialogue with fashion designers and professors, encouraging them to reevaluate their practices and foster imagination.
Keywords: scenarios; Melissa; fashion collection development